Mangrove Habitat Structure of Mud Crabs (Scylla serrata and S. olivacea) in the Bee Jay Bakau Resort Probolinggo, Indonesia - Audina Putri; Dietriech Geoffrey Bengen; Neviaty Putri Zamani; Ummu Salma; Novian Prahandhy Kusuma; Nanda Tiara Diningsih; Sonja Kleinertz (Marine Science Department Diponegoro University, 2022)
Mud crabs (Scylla serrata and S. olivacea) are important fisheries resources, but their population in nature is decreasing due to anthropogenic activities, like the deforestation of mangrove forests. Hence, it is crucial to conserve this marine biota for future sustainable use and to conserve our marine biodiversity. Conducting studies on the biological interactions of mud crabs in mangrove habitats can be one of the future conservation approaches. Accordingly, an analysis of the functional relationships between Scylla spp. abundance and the respective mangrove habitat have to be carried out. The research was conducted in the mangrove ecosystem of Bee Jay Bakau Resort Probolinggo (BJBR). Data were collected using line transects and quadrant transects. The Associations between mangroves and mud crab habitat structures were analyzed using the Correspondence Analysis (CA) method. The results show that the relationship matrix between Scylla spp. and the structure of the mangrove habitat is centered on the F1 and F2 factorial axes (89.22%). S. serrata of all size classes were associated with dense mangroves (≥15 trees per 100m2) and high salinities (3-4 ppt), while S. olivacea has shown to be associated with rare to very dense mangrove systems. It indicates that S. olivacea tends to have a higher adaptation rate than S. serrata in this mangrove system. This study will provide information and recommendation for the conservation management of mud crabs and mangrove ecosystems to conserve marine biodiversity.